REAKSI INVESTOR DALAM PASAR MODAL TERHADAP TERPILIHNYA INDONESIA SEBAGAI TUAN RUMAH ASIAN GAMES TAHUN 2018 (EVENT STUDY PADA PERUSAHAAN YANG TERDAFTAR DI LQ45 DI BURSA EFEK INDONESIA) - Elisabet Susianti Ningrum; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThe purpose of this study was to analyze the investor’s reaction in the capital market from the impact of the selection of Indonesia as an Asian Games household in 2018, which will be indicated by the presence or absence of abnormal return and trading volume activity. The population used is the stock of LQ 45 at BEI. The sampling technique was done by purposive sampling method. This study is event study so that the observation period will see the reaction on before and after the event. In this study period used was H-5 (before the event) and H+5 (after the event).The data used in this research is secondary data, such as the closing price of shares has been adjusted and the closing price of IHSG. Data in the form of daily stock price. The data was then analyzed using analytical methods paired sample t-test. The result showed that when viewed from the average abnormal return (AAR) and trading volume activity (TVA) did not show any difference between before and after the event.Keywords: Average Abnormal Return, Trading Volume Activity, Event Study